Tanggapan Pengarang Riau terhadap budaya bandar di Pulau Jiran - Putten, Jan Van Der (Universiti Kebangsaan Malaysia, 2007)
This is a study of Syair Ghayat al-Muna, a poem written by Abu Muhammad Adnan, a member of the nobility in Pulau Penyengat and an intellectual of the Riau Islands. He wrote or translated the poem for the burgeoning printing industry in Singapore. This indigenous printing industry was in the hands of several ethnic groups, contributing to the forging of new identities, such as the Javanese, Indian Muslims and later, Malays from the islands. However, competition from the colonial and capital-intensive printing firms eventually proved too stiff, and Malay printing petered out (for the time being). The indigenous lithographic presses were located at Kampung Gelam, near Rochor River, where the Muslim trade and pilgrimage firms were concentrated, and with which the printing was intimately connected. In Singapore a hybrid culture rapidly developed during this period. Foreign books and magazines circulated freely and Malay translations appeared on the book market. Several new hybrid art forms appeared and rose to popularity, such as Baba pantuns, film and bangsawan theatre. The syair discussed here should be interpreted in relation and as a reaction to the developing urban culture that had spilled over onto neighbouring islands: it was written or translated for the printing industry and the story was part of the repertoire of the bangsawan theatre. Furthermore, the way the story is presented, with personification of the different parties involved in the literary process (narrator, pen, ink, etc.) and with the inclusion of illustrations in the manuscript to support the story visually, is reminiscent of Syed Sheikh al-Hadi’s book published in the 1920s. Therefore, a discussion about the originality of his Hikayat Faridah Hanom should not only be focused on the Arabic original, but should more importantly look into the cultural atmosphere in Singapore at the turn of the century